2015
DOI: 10.1105/tpc.114.135731
|View full text |Cite
|
Sign up to set email alerts
|

Specific Membrane Lipid Composition Is Important for Plasmodesmata Function in Arabidopsis

Abstract: Plasmodesmata (PD) are nano-sized membrane-lined channels controlling intercellular communication in plants. Although progress has been made in identifying PD proteins, the role played by major membrane constituents, such as the lipids, in defining specialized membrane domains in PD remains unknown. Through a rigorous isolation of "native" PD membrane fractions and comparative mass spectrometry-based analysis, we demonstrate that lipids are laterally segregated along the plasma membrane (PM) at the PD cell-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
224
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(246 citation statements)
references
References 127 publications
(210 reference statements)
19
224
3
Order By: Relevance
“…It was found recently that the region of the PM that lines the Pd channel is highly enriched in sphingolipids and sterols (Grison et al, 2015). Moreover, it was shown that Pd localization of GPI-APs, like PDCB1 and PDBG2, could be disrupted by inhibiting the sterol biosynthesis pathway (Grison et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found recently that the region of the PM that lines the Pd channel is highly enriched in sphingolipids and sterols (Grison et al, 2015). Moreover, it was shown that Pd localization of GPI-APs, like PDCB1 and PDBG2, could be disrupted by inhibiting the sterol biosynthesis pathway (Grison et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was found recently that the region of the PM that lines the Pd channel is highly enriched in sphingolipids and sterols (Grison et al, 2015). Moreover, it was shown that Pd localization of GPI-APs, like PDCB1 and PDBG2, could be disrupted by inhibiting the sterol biosynthesis pathway (Grison et al, 2015). In addition, proteomic analysis of sterol-enriched detergent-resistant membranes in Arabidopsis revealed that GPI-APs are overrepresented in those membranes (Kierszniowska et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipids are also thought to affect the structure and function of PD (Delage and Zurzolo, 2013), but little is known about the lipid constituents of PD. Grison et al (2015) analyzed the lipid composition of membranes lining primary PD using highly purified PD-derived membranes from Arabidopsis thaliana suspension cells. A comparative mass spectrometry-based analysis showed that the lipid composition of PD membranes differed from that of the surrounding plasma membrane, with PD membranes being enriched in sterols and complex sphingolipids with very long saturated fatty acid tails.…”
mentioning
confidence: 99%